The effects of selenium, vitamin E and their combination on the composition of fatty acids and proteins in Saccharomyces cerevisiae - Dilsiz, N; Celik, S; Yilmaz, O; Digrak, M (John Wiley & Sons Ltd, 1997)
The aim of our studies was to test the effect and role of vitamin E and selenium supplements on yeast cell. In this study, the effects of selenium (Se), vitamin E (Vit. E), and their combination (Se plus Vit. E) on the composition of fatty acids and proteins were examined in Saccharomyces cerevisiae strains WET136 and 522. S. cerevisiae cells were grown up in YEPD medium supplemented with Se, Vit. E or their combination. It was found that the level of stearic acid was increased in all supplemented groups (p < 0.05; p < 0.001). The content of saturated and unsaturated fatty acids was decreased (p < 0.05; p < 0.01; p < 0.001) in Vit. E and Vit. E plus Se supplemented S. cerevisiae. On the other hand, Se alone caused an increase (p < 0.001)in the saturated fatty acids but a decrease (p < 0.05; p < 0.001) in the unsaturated fatty acids. Total proteins in S. cerevisiae were significantly increased (p < 0.001) by Vit. E supplement. There was no significant change observed in S. cerevisiae supplemented with Se. These findings indicate that membrane composition of S. cerevisiae is affected by both Vit. E and Se supplements. (C) 1997 John Wiley & Sons, Ltd.
Keywords: selenium; vitamin E; fatty acids; proteins; Saccharomyces cerevisiae